Investigations on Maize in the Libyan Arab Republic: II. Effect of Nitrogen Level and Time of Application on Growth and Yield of Maize (Zea mays L.) - EL-SHARKAWY, M. A.; SGAIER, K.; SOROUR, F. A .; YOUSEF, M. E. (The Libyan Journal of Agriculture, 2023)
The influence of nitrogen level and system of application on growth and yield of the open-pollinated Early American maize variety was investigated under the agro-climatic factors of Tripoli, Libya, over two years (1972 and 1973). Increasingjiitrogen level up to 126 kgN/ha significantly increased yields of grain and stover, size of kernels, diameter and length of topmost ear. Also diameter and height of plants were significantly increased by nitrogen treatments. Application of nitrogen in two and three equal split dressings gave higher grain and stover yields than in a single dressing. Also, size of kernels, topmost ear diameter, length and height, as well as stalk height and diameter were increased by split dressings over the single applications. The highest grain yields of 7.33 and 6.80 tons/ha; and stover yields of 13.64 and 11.90 tons/ha were obtained in 1972 and 1973, respectively, when nitrogen was added at 126 kgN/ha in three equal split applications at 18, 33, and 45 days after planting.